2020
DOI: 10.1007/s00418-020-01894-6
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic VDR expression as an independent risk factor for ovarian cancer

Abstract: The vitamin D receptor (VDR), primarily known as a crucial mediator of calcium homeostasis and metabolism, has been shown to play a significant role in various cancer entities. Previous studies have focused on vitamin D and its receptor in gynecological cancers, noting that the receptor is upregulated in epithelial ovarian cancer (EOC). The aim of this study is to analyze the prognostic impact of VDR and its functional significance in ovarian cancer. Through immunohistochemistry, VDR staining was examined in 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 49 publications
1
20
0
1
Order By: Relevance
“…However, THR has been identified to show cancer-promoting activities during BC development [24]. In the case of VDR, a direct link between the cytoplasmic localization of VDR and impaired OS in ovarian cancer has been reported [25]. Furthermore, higher cytoplasmic VDR expression in colon and vulvar cancer, as well as in malignant melanoma, had an impact on tumor progression and prognosis [66][67][68].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, THR has been identified to show cancer-promoting activities during BC development [24]. In the case of VDR, a direct link between the cytoplasmic localization of VDR and impaired OS in ovarian cancer has been reported [25]. Furthermore, higher cytoplasmic VDR expression in colon and vulvar cancer, as well as in malignant melanoma, had an impact on tumor progression and prognosis [66][67][68].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the role of NR in distinct intracellular compartments indicate a specific prognostic value, depending on the subcellular localization [24]. Czogalla et al demonstrated a direct link between the cytoplasmic localization of VDR and impaired overall survival (OS) in ovarian cancer [25]. In the case of THR, high nuclear localization was reported to be a positive predictive factor for OS in epithelial ovarian cancer [22].…”
Section: Introductionmentioning
confidence: 99%
“…LXR [ 283 285 ], PXR [ 286 ], VDR [ 287 296 ] or CAR [ 297 , 298 ] activation was shown to exert protective features against ovarian cancer, similar to BA-elicited effects suggesting that BAs may have a more profound role in protecting against ovarian cancer. These protective effects involved the suppression of proliferation [ 283 , 284 , 286 ], invasion [ 291 ], EMT [ 288 ], de novo fatty acid biosynthesis [ 295 ], the proportions of the cancer stem cell population [ 289 ], and the improvement of the efficacy of chemotherapy [ 285 , 297 , 298 ] culminating in better patient survival [ 292 , 293 ].…”
Section: Effects Of Bile Acids In Cancersmentioning
confidence: 99%
“…(5) clear cell histology. Given the heterogeneity of ovarian cancer subtypes, Czogalla et al (2020) have performed an immunohistochemical analysis of VDR in these subtypes, with the aim of correlating expression with patient survival. VDR immunoreactivity was detected in both the nucleus and cytoplasm as expected.…”
Section: Vitamin D Receptor (Vdr) Expression As a Potential Prognostic Marker For Ovarian Cancermentioning
confidence: 99%
“…CI confidence interval, FIGO Fédération Internationale de Gynécologie et d'Obstétrique stage. From Czogalla et al (2020)…”
Section: Vitamin D Receptor (Vdr) Expression As a Potential Prognostic Marker For Ovarian Cancerunclassified